To simplify the expression \( \sqrt{4396} + \sqrt{44} - \sqrt{2275} \), we first simplify each radical where possible.
-
Simplifying \( \sqrt{4396} \):
- Factor \( 4396 \): \[ 4396 = 4 \times 1099 \] Therefore, \[ \sqrt{4396} = \sqrt{4 \times 1099} = \sqrt{4} \times \sqrt{1099} = 2\sqrt{1099} \]
-
Simplifying \( \sqrt{44} \):
- Factor \( 44 \): \[ 44 = 4 \times 11 \] Hence, \[ \sqrt{44} = \sqrt{4 \times 11} = \sqrt{4} \times \sqrt{11} = 2\sqrt{11} \]
-
Simplifying \( \sqrt{2275} \):
- Factor \( 2275 \): \[ 2275 = 25 \times 91 = 25 \times (7 \times 13) \] So, \[ \sqrt{2275} = \sqrt{25 \times 91} = \sqrt{25} \times \sqrt{91} = 5\sqrt{91} \]
Now, substitute the simplified radicals back into the expression:
\[ \sqrt{4396} + \sqrt{44} - \sqrt{2275} = 2\sqrt{1099} + 2\sqrt{11} - 5\sqrt{91} \]
Since \( 2\sqrt{1099} \), \( 2\sqrt{11} \), and \( 5\sqrt{91} \) are unlike radicals, we can't combine them further. Thus, the final answer, in simplest radical form, is:
\[ 2\sqrt{1099} + 2\sqrt{11} - 5\sqrt{91} \]
Since the provided responses do not yield an accurate representation of the solution and none of the options reflect the final simplified expression, the correct conclusion here is that this sum cannot be simplified further and remains expressed as above. If choosing from the given responses, it would simply be noted that unlike radicals cannot be combined using addition.